Perceived sharia compliance and gen Z intention to use pegadaian syariah digital application: An extended technology acceptance model - Danial Muhammad Wirdyansyah; Annisa Nur Salam; Muhammad Wijdan Nur Rohman (The Journal of Religion and Communication Studies, 2026)
Background: Digital sharia gold pawn services are increasingly adopted by Generation Z; however, the theoretical explanation of adoption behavior in Islamic digital finance remains limited. Prior technology adoption studies, largely grounded in conventional Technology Acceptance Models (TAM), tend to emphasize usability and functional benefits, while overlooking the roles of institutional trust, confidence, and religious legitimacy that are central to sharia-based financial services. This study aims to examine the determinants of behavioral intention to use digital sharia gold pawn services by extending the Technology Acceptance Model (TAM) with sharia-specific and confidence-based constructs. Methods: This study employs a quantitative survey design based on an extended TAM framework. Data were collected from Generation Z users of digital sharia gold pawn services using purposive non-probability sampling. The minimum sample size was determined using the inverse square root criterion for PLS-SEM, and a total of 433 valid responses were obtained. The proposed model was analyzed using partial least squares structural equation modeling (PLS-SEM). Findings: The results indicate that behavioral intention is primarily driven by confidence-based and institutional factors rather than usability-oriented considerations. User confidence emerges as the strongest predictor of adoption, followed by perceived sharia compliance, facilitating conditions, and perceived usefulness. In contrast, perceived ease of use, perceived risk, and social influence exhibit limited explanatory power. Conclusion: These findings suggest a shift in technology acceptance behavior among digitally mature users toward trust, legitimacy, and institutional assurance in Islamic digital financial services. Novelty/Originality of this article: This study contributes to the literature by extending TAM with sharia compliance and user confidence constructs and by conceptualizing digital sharia pawnshops as trust-intensive hybrid institutions within the Islamic financial technology ecosystem.